2014
DOI: 10.1007/s10903-014-0067-y
|View full text |Cite
|
Sign up to set email alerts
|

HPV Awareness and Vaccine Willingness Among Dominican Immigrant Parents Attending a Federal Qualified Health Clinic in Puerto Rico

Abstract: The purpose of this study was to describe the socio-demographic characteristics, awareness of human papillomavirus (HPV), and willingness to vaccinate among a convenience sample of 60 immigrant Dominican parents of adolescent sons in a Federal Qualified Health Clinic (FQHC) in Puerto Rico (PR). Participation involved completing a self-administered survey. Even though more than half of the parents had not received proper HPV vaccine orientation from healthcare provider (58.3%) nor asked provider for vaccination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 11 publications
3
30
0
Order By: Relevance
“…Twelve studies were conducted in the USA, three in the UK, one in the Netherlands, one in Denmark, one in Sweden, and one in Puerto Rico. Six studies were conducted in community organizations including faith-based centres like churches and mosques [21][22][23][24][25][26], eight in health and social service agencies [27][28][29][30][31][32][33][34], two in schools and/or community groups [35,36], another two in social clubs [37,38], and one in a household [39].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies were conducted in the USA, three in the UK, one in the Netherlands, one in Denmark, one in Sweden, and one in Puerto Rico. Six studies were conducted in community organizations including faith-based centres like churches and mosques [21][22][23][24][25][26], eight in health and social service agencies [27][28][29][30][31][32][33][34], two in schools and/or community groups [35,36], another two in social clubs [37,38], and one in a household [39].…”
Section: Resultsmentioning
confidence: 99%
“…For knowledge, the level of parents' knowledge about HPV disease and HPV vaccine ranged from no knowledge in 11 studies [21][22][23][24]26,27,29,33,35,37,39] to limited knowledge regarding HPV and HPV vaccine, as they heard about the vaccine but they did not know HPV vaccine's purpose, the eligibility requirements for the vaccine, and the vaccine's dosing/schedule requirements in three studies. Five studies revealed that some participants had not heard of HPV disease or HPV vaccine [27,33,35,39]. There were four studies that reported participants had no prior knowledge of HPV as a sexually transmitted disease or as a cause of cancer [25,30,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This manual search yielded two additional eligible studies. In total, 11 articles were selected for final inclusion in this integrative review [29][30][31][32][33][34][35][36][37][38][39].…”
Section: Selection Of Articlesmentioning
confidence: 99%
“…According to Whittemore and Knafl, there is no gold standard for assessing the methodological quality of studies included in an integrative review [27]. For the current review, the quality of each included study was reviewed independently by two authors (ACL, SFW, MLG) using the criteria from the validated Critical Appraisal Skills Program (CASP) quality framework tool [40] for qualitative [29,39], quantitative [31,32,36,38] and mixed methods studies [30,33,34,35,37]. The CASP qualitative tool is comprised of 12 questions [40] and 10 of them were used to appraise mixed methods studies (n=6) and qualitative studies (n=2) included in this review (see Table 1).…”
Section: Quality Appraisalmentioning
confidence: 99%